A Queensland research support network in emergency healthcare: Collaborating to build the research capacity of more clinicians in more locations. Issue 1 (10th January 2019) - Sweeny, Amy; van den Berg, Lisa; Hocking, Julia; Renaud, Julia; Young, Sharleen; Henshaw, Richard; Foster, Kelly; Howell, Tegwen
Abstract : Purpose: The purpose of this paper is to describe the structure and impact of a Queensland Research Support Network (RSN) in emergency medicine (EM). Design/methodology/approach: This paper presents a descriptive summary of EM networks, network evaluations and the structure and development of the Emergency Medicine Foundation's (EMF) RSN in Queensland, including an observational pre- and post-study of research metrics. Findings: In two years, the RSN supported 33 Queensland emergency departments (EDs), of which 14 developed research strategies. There was an increase in research active clinicians, from 23 in 2015 to 181 in 2017. Collaborator engagement increased from 9 in 2015 to 276 in 2017 as did the number of research presentations, from 6 in 2015 to 61 in 2017. EMF experienced a growth in new researchers, with new investigators submitting approximately 60 per cent of grant applications in 2016 and 2017. EMF also received new applications from a further three HHS (taking EMF-funded research activity from 8 to 11 HHS). Research limitations/implications: This paper describes changes in KPIs and research metrics, which the authors attribute to the establishment of the RSN. However, it is possible that attribution bias plays a role in the KPI improvements. Social implications: This network has actively boosted and expanded EM research capacity and capability in Queensland. It provides services, in the form of on-the-ground managers, to develop novice clinician-researchers, new projects and engage entire EDs. This model may be replicated nationwide but requires funding commitment. Originality/value: The RSN improves front-line clinician research capacity and capability and increases research activity and collaborations with clear community outcomes. Collaborations were extended to community, primary health networks, non-government organisations, national and international researchers and academic institutions. Evaluating and measuring a network's benefits are difficult, but it is likely that evaluations will help networks obtain funding.